Distinct Short‐Range Order Is Inherent to Small Amorphous Calcium Carbonate Clusters (<2 nm). Issue 40 (9th September 2016) - Sun, Shengtong; Chevrier, Daniel M.; Zhang, Peng; Gebauer, Denis; Cölfen, Helmut
Abstract: Amorphous intermediate phases are vital precursors in the crystallization of many biogenic minerals. While inherent short‐range orders have been found in amorphous calcium carbonates (ACCs) relating to different crystalline forms, it has never been clarified experimentally whether such orders already exist in very small clusters less than 2 nm in size. Here, we studied the stability and structure of 10, 12‐pentacosadiynoic acid (PCDA) protected ACC clusters with a core size of ca. 1.4 nm consisting of only seven CaCO3 units. Ligand concentration and structure are shown to be key factors in stabilizing the ACC clusters. More importantly, even in such small CaCO3 entities, a proto‐calcite short‐range order can be identified but with a relatively high degree of disorder that arises from the very small size of the CaCO3 core. Our findings support the notion of a structural link between prenucleation clusters, amorphous intermediates, and final crystalline polymorphs, which appears central to the understanding of polymorph selection. Abstract : Proto‐calcite short‐range order was found in ligand‐stabilized amorphous calcium carbonate clusters with a very small CaCO3 core 1.4 nm in diameter consisting of only seven CaCO3 units. This supports the notion of a structural link between prenucleation clusters and the postnucleation amorphous phase.